Climate and fundamentals of the energy offer in Cape Verde - Jorge Tavares; Myriam Lopes; Fernando Neto (Energy Reports, 2020)
In Cape Verde, despite the existence of an exceptional renewable potential, namely wind and solar photovoltaic, estimated, by Gesto (2011), at 258 MW and 315 MW respectively, in 2017 82.2% of the electric energy was generated using fossil fuels. In this work, we propose to explore the fundamentals of energy offer and the relationship with climate change, taking Cape Verde as a case study, analyzing the determinant aspects for the diversification of the energy offer, taking into account an augmented role of renewable resources and the main market mechanisms and exploring aspects such as the energy infrastructures. It is also proposed to create an ARIMA model based on the available data to evaluate the behavior of the Capeverdian energy system in terms of consumption of fossil fuels.
Keywords: 330; Sustainability; Energy; ARIMA; Climate